Dispersion of latencies in photoreceptors of Limulus and the adapting- bump model (The Rockefeller University Press, 1980)
To light stimuli of very low intensity, Limulus photoreceptors give a voltage response with a fluctuating delay. This phenomenon has been called "latency dispersion." If the generator potential is the superposition of discrete voltage events ("bumps"), and if the effect of light upon bump size is negligible, then the latency dispersion and the bump shape completely characterize the frequency response to sinusoidal flicker. For very low light intensities, the latency dispersion of the bumps, the bump shape, and the frequency response are measured. It is found that for data obtained at 20 degrees C, the frequency response can be accounted for completely by the latency dispersion and by the bump shape derived from steady-state noise characteristics. At 10 degrees C, the time scale of the response of the photoreceptor is lengthened. The dispersion of latencies and the bump shape are found not to have the same temperature dependence. However, just as those measured at 20 degrees C, the bump shape and the dispersion of latencies measured at 10 degrees C can predict the frequency response measured under the same conditions. These results strongly suggest that the major mechanisms involved in the generator potential are the latency process and the bump process. At high light intensities, the time scale of the generator potential shortens. The decrease in time scale of the generator potential can be attributed to the decreases in time scales of the bumps and of the latency dispersion process.